The impact of differentiated assessment on teaching and learning: multi-case studies of PutraPacer application in a higher education institution - Majuddin, Christye; Md Khambari, Mas Nida (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Acknowledging the diversity of learners in the 21st century, differentiation need to be integrated in classroom instruction and assessment. There are researches on differentiated assessments that have been carried out in Malaysia. These researches featured strategies and the usage of different tools to carry out differentiation in teaching and learning. However, to date, there is no generic, systematic and dedicated tools available yet for teachers or lecturers to achieve and employ alternative assessment for differentiated classroom. Hence, PutraPacer is developed as a customizable intelligent web application for differentiated assessment. The purpose of this research is to explore the impact of PutraPacer as a differentiated assessment tool on teaching and learning in the higher education. This is a multi-case study which will be carried out on three experienced lectures from different streams, together with their respective students. The outcome of this research should be able to enrich the practice of differentiated assessment in the field of education and at the same time providing another alternative to assessing mixed-ability classroom with a more comprehensive and systematic tool.